ChemInform Abstract: Palladium‐Catalyzed Oxidative Synthesis of Unsymmetrical Azophenols. Issue 29 (29th June 2016) - Nguyen, Thi Hong Long; Gigant, Nicolas; Delarue‐Cochin, Sandrine; Joseph, Delphine
Abstract: A new method for the ortho‐directed hydroxylation of both symmetrical and unsymmetrical azobenzenes is developed.